Mechanical Properties Modification of Polyethylene (PE) for CaCO3 Particulated Composites - Sivarao, Subramonian; Mohd Rizal , Salleh; Ahmad, Kamely; Tajul Ariffin, Abdullah; Taufik, - (Trans Tech Publications, 2011)
Calcium carbonate (CaCO3) is one of the most useful and versatile materials known to man. In this research, eggshell as a natural composite bioceramics was used to modify and improve the mechanical properties of an existing polyethylene which is widely used to manufacture daily goods by small medium industries in Malaysia. Chicken eggshell containing 95% Calcium Carbonate is highly potential to be used as bio-filler to improve poly-based matrix in improving their performance behavior. PE was chosen for this project to modify its virgin mechanical properties by reinforcing eggshell/calcium carbonate and later investigate its character to improve the current product’s performance. Tensile, creep and flexural tests were carried out to characterize the developed PE-CaCO3 composites. Eggshells which were prepared into hundreds of microns and furnace dried at 90oC continuously for eight hours to improve the bonding capability. They were then particulated into polyethylene matrix accordingly as per the designed weight ratios, 10%, 20%, 30% and 40%. From the result, it was learnt that the ES filler has improved mechanical properties of virgin PE as far as 5% to 9% depending on the filler weight ratio. Therefore, ES which was a burden for disposal and being environmental threat can now be used for the betterment of PE product performance.